2021
DOI: 10.1021/acs.nanolett.1c01651
|View full text |Cite
|
Sign up to set email alerts
|

Percolation of Ion-Irradiation-Induced Disorder in Complex Oxide Interfaces

Abstract: Mastery of order–disorder processes in highly nonequilibrium nanostructured oxides has significant implications for the development of emerging energy technologies. However, we are presently limited in our ability to quantify and harness these processes at high spatial, chemical, and temporal resolution, particularly in extreme environments. Here, we describe the percolation of disorder at the model oxide interface LaMnO3/SrTiO3, which we visualize during in situ ion irradiation in the transmission electron mi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Therefore, XRR in combination with XRD suggests a significant modification in the microstructural properties both at layer structure length (with sub-nanometer depth resolution) and atomic (XRD) length scale (microstrain growth) due to SHI irradiation. However, the crystalline structure (pseudo-cubic perovskite) of the LPCMO films remains integral to ion irradiation, which is consistent with other studies [30][31][32][33][34].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, XRR in combination with XRD suggests a significant modification in the microstructural properties both at layer structure length (with sub-nanometer depth resolution) and atomic (XRD) length scale (microstrain growth) due to SHI irradiation. However, the crystalline structure (pseudo-cubic perovskite) of the LPCMO films remains integral to ion irradiation, which is consistent with other studies [30][31][32][33][34].…”
Section: Resultssupporting
confidence: 91%
“…The influence of SHI irradiation on the magnetic proximity effect in oxidebased manganite/superconductor heterostructure has also been demonstrated as a modification in structure, magnetic, and superconducting properties upon irradiation [36]. Recently, Matthews et al [34] observed the formation and percolation of a network of disorder in the LaMnO 3 /SrTiO 3 heterostructures on ion irradiation, which led to a change in structural and morphological properties at interfaces. Using x-ray resonant magnetic scattering (XRMS), Singh et al [16,17] correlated the electronic and magnetic phases across MIT temperature of the (La 1-y Pr y ) 1-x Ca x MnO 3 thin film with x = 0.375 and y = 0.6 and found that these properties are highly dependent on the morphology of the interfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10] Under the irradiation of 2.8 MeV Au ion, a percolation of the disordered crystalline phase at the interface of LaMnO 3 and SrTiO 3 is observed. 11 All these findings highlight the importance of a detailed understanding of atomic arrangement to determine the phase transformation mechanisms resulting from ion-irradiation events, which is the focus of the present work. Our interest and focus of the present work is the development of an atomic-level understanding of the structural transformation induced by individual swift heavy ions (energy larger than 50 MeV) in SrTiO 3 that is a well-known wide-bandgap material and described as a critical foundational material in the area of functional oxide electronics.…”
Section: Introductionmentioning
confidence: 76%
“…These capabilities are now being used in nuclear materials research (Clark et al, 2020;Popel et al, 2020;Müller et al, 2021). Here we highlight a few examples: AC-STEM-EELS has been used to characterize the ion irradiated LaMnO 3 /SrTiO 3 interface and the oxidation of UO 2 at atomic resolution to describe subtle changes in structure over nanometer-sized regions (Spurgeon et al, 2019;Matthews et al, 2021). The process of amorphization in nuclear materials considered for the immobilization of plutonium, such as zirconolite (CaZrTi 2 O 7 ) and zircon (ZrSiO 4 ), has been monitored through in-situ ion irradiation in the electron microscope (Weber et al, 1994;Wang et al, 2000).…”
mentioning
confidence: 99%